The Potential of Forest Waqf as an Islamic Social Financial Instrument in Mitigating Climate Crisis - Niko Faiz Fahrezi (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
The global climate crisis has intensified the urgency to develop sustainable and ethical environmental protection models. Deforestation, a major contributor to greenhouse gas emissions, has led to severe ecological and socio-economic consequences. In Indonesia, where forest biodiversity is critical to ecosystem stability and community livelihoods, innovative solutions rooted in local values are essential. This study aims to examine the potential of forest waqf as a strategic model within Islamic social finance to address environmental degradation and promote sustainable development. Using a qualitative research design with a library research approach, this study analyzes data obtained from journal articles, government reports, and official publications. The findings reveal that forest waqf through mechanisms such as agroforestry, ecotourism, and sustainable land management offers a dual function in ecological restoration and community empowerment. Case studies from Aceh and Bogor highlight the model’s effectiveness in reforesting degraded land while generating income for local populations. However, challenges remain, including limited public awareness, governance gaps, and regulatory barriers. Strategic recommendations include improving legal frameworks, integrating digital tools, and fostering multi-sectoral collaboration. Overall, forest waqf represents a promising solution for climate action that aligns with religious, ecological, and economic values, and could be expanded to other biodiversity-rich regions.